2008
DOI: 10.1097/sla.0b013e31815aaadf
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Metastatic Lymph Nodes and the Ratio Between Metastatic and Examined Lymph Nodes Are Independent Prognostic Factors in Esophageal Cancer Regardless of Neoadjuvant Chemoradiation or Lymphadenectomy Extent

Abstract: Staging systems for esophageal cancer that use the number (< or =4 or >4) and the ratio (< or =0.2 or >0.2) of LNMs have greater prognostic importance than the current staging systems because of the good stratification of the groups and their clinical utility, taking into account neoadjuvant therapy and lymphadenectomy extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
239
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(262 citation statements)
references
References 30 publications
19
239
2
2
Order By: Relevance
“…Patients with a lymph node ratio of less than 0.2 have a significantly better prognosis [54,94,96,97] with a reported ratio range from 0.1 [87,98] to 0.3 [97]. When comparing a lymph node ratio of less than 0.2 with greater than 0.2, it has been shown that the 5-year survival falls from 54% to 22% and the risk of recurrence rises from 44% to 69% [89]. This discrepancy in the value of the cut-off ratio is likely due to the fact that a more extensive lymphadenectomy leads to a greater number of uninvolved nodes being resected and thus reducing the cut-off ratio [94].…”
Section: Lymph Node Ratiomentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with a lymph node ratio of less than 0.2 have a significantly better prognosis [54,94,96,97] with a reported ratio range from 0.1 [87,98] to 0.3 [97]. When comparing a lymph node ratio of less than 0.2 with greater than 0.2, it has been shown that the 5-year survival falls from 54% to 22% and the risk of recurrence rises from 44% to 69% [89]. This discrepancy in the value of the cut-off ratio is likely due to the fact that a more extensive lymphadenectomy leads to a greater number of uninvolved nodes being resected and thus reducing the cut-off ratio [94].…”
Section: Lymph Node Ratiomentioning
confidence: 99%
“…These modifications reflect findings which show improved prognostic stratification with consideration of the number ofdiseased lymph nodes [13,[84][85][86]. Several studies have shown the number of positive lymph nodes to be an independent prognostic indicator [13,14,[87][88][89][90]. …”
Section: Number Of Positive Lymph Nodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, among the stage III patients, there was a higher percentage of pN2 in the group of patients with more than 12 LN in the surgical specimen (p = 0.100). The metastatic LNR, which was initially proposed for patients with esophageal and gastric cancer [40,41], is expected to yield a more reliable prognosis. Several recent studies have investigated the role of the LNR in colorectal cancer; however, few reported on rectal cancer and none on laparoscopic resection.…”
Section: Discussionmentioning
confidence: 99%